Preparation method of nanofiber for deeply removing copper complex and application of nanofiber in aspect of recycling wastewater containing copper complex

Electrospun nanofibers modified with polyacrylonitrile and polyaniline effectively remove and recover copper complexes from wastewater, addressing inefficiencies in existing treatments by achieving high adsorption capacity and resource recovery.

CN119158554APending Publication Date: 2024-12-20CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411582211.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Current copper complex wastewater treatment technologies, such as chemical precipitation, ion exchange, electrochemical treatment, and membrane separation, are inadequate in efficiently removing and recovering copper complexes due to their toxicity and non-biodegradability, posing health and environmental risks.

Method used

A method using electrospinning technology to produce nanofibers from polyacrylonitrile, polyaniline, and polypropylene, modified with alkenyl nitrile and hydroxylamine hydrochloride, creating a nanomaterial adsorbent with high affinity for copper complexes, enabling deep removal and resource recovery through adsorption and desorption processes.

Benefits of technology

The nanofibers achieve high adsorption capacity (up to 372.6 mg/g) and equilibrium in 120 minutes, with effective copper complex removal and regeneration, allowing for resource recovery as copper sulfate products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158554A_ABST
    Figure CN119158554A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbent materials, and particularly relates to a preparation method of nanofibers for deeply removing a copper complex and application of the nanofibers in the aspect of recycling copper-complex-containing wastewater, and the preparation method comprises the following steps: (1) modifying by taking a high-molecular polymer polyacrylonitrile, polyaniline or polypropylene as a raw material; and (2) carrying out electrostatic spinning operation on the modified polyacrylonitrile, polyaniline or polypropylene to obtain the nanofiber. According to the preparation method, polyacrylonitrile, polyaniline and polypropylene are taken as raw materials, a nitrile polymerization monomer and hydroxylamine hydrochloride are taken as adsorption modification materials, the amidoxime-based nanofiber adsorbent is obtained through an electrostatic spinning technology, and the amidoxime-based nanofiber adsorbent has an extremely high adsorption and purification effect on copper-containing complex wastewater; a copper sulfate product can be prepared by concentrating, cooling, crystallizing, filtering and drying the copper complex desorption solution, so that recycling of the wastewater containing the copper complex is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent materials, and specifically relates to a method for preparing nanofibers for deep removal of copper complexes and an application in resource recovery of wastewater containing copper complexes. Background Art

[0002] Copper complex wastewater mainly comes from industrial production processes, especially those involving copper metal processing, electroplating, circuit board manufacturing, printing and dyeing, etc. It is highly toxic and non-biodegradable, and has an important impact on human health and environmental safety.

[0003] Currently, the more commonly used copper complex wastewater treatment technologies include chemical precipitation, ion exchange, electrochemical treatment, membrane separation technology and adsorption technology. Among them, adsorption technology has the characteristics of simple operation and good treatment effect, especially the emergence of some modified adsorption materials, which greatly improves the removal efficiency of copper complexes.

[0004] Electrospinning technology is a special, efficient and environmentally friendly fiber manufacturing process that can adjust the fiber diameter within a wide range to prepare nano-fiber materials with high specific surface area and fine pore size. This material can achieve efficient adsorption effects in wastewater treatment that are unmatched by other adsorbents. Summary of the invention

[0005] The present invention aims to solve at least one of the problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing nanofibers for deep removal of copper complexes and its application in resource recovery of wastewater containing copper complexes. The present invention uses polyacrylonitrile, polyaniline and polypropylene as raw materials, and uses alkenyl nitrile and hydroxylamine hydrochloride as adsorption modification materials through modification. A nanomaterial adsorbent with strong affinity for copper complexes is obtained through electrostatic spinning technology, which exhibits extremely high adsorption and purification effects on wastewater containing copper complexes, and the wastewater containing copper complexes is recovered as a resource to obtain copper sulfate products.

[0006] To achieve the above object, the first aspect of the present invention provides a method for preparing nanofibers for deep removal of copper complexes, comprising the following steps:

[0007] (1) Modification using high molecular weight polymers such as polyacrylonitrile, polyaniline or polypropylene as raw materials;

[0008] (2) The nanofibers are obtained by electrospinning modified polyacrylonitrile, polyaniline or polypropylene through static solution electrospinning.

[0009] Specifically, in the step (1), polyacrylonitrile, polyaniline or polypropylene is dissolved to prepare a corresponding solution; preferably, polyacrylonitrile is dissolved in N,N-dimethylformamide at a dissolution temperature of 70 to 120°C, polyaniline is dissolved in N,N-dimethylformamide at a dissolution temperature of 75 to 100°C, and polyaniline is dissolved in N,N-dimethylformamide at a dissolution temperature of 75 to 100°C.

[0010] Furthermore, the modification is specifically as follows: when the raw material is polyacrylonitrile, it is directly modified using hydroxylamine hydrochloride; when the raw material is polyaniline or polypropylene, it is first modified by nitrile grouping and then modified using hydroxylamine hydrochloride.

[0011] Specifically, the nitrile modification is achieved by reacting polyaniline or polypropylene with alkenyl nitrile compounds and an initiator, the modification temperature is 50-90° C., and the modification time is 2-12 hours; the initiator is any one of potassium persulfate, ammonium persulfate, sodium persulfate, azobisisobutyronitrile and dicumyl peroxide, or a mixture of several of them, and the amount of the initiator is 0.1%-2% of the mass of the polyaniline or polypropylene; the alkenyl nitrile compound is any one of acrylonitrile, butadiene dinitrile, butenenitrile, acrylonitrile, pentenenitrile, 3-cyclohexene-1-nitrile and methacrylonitrile, or a mixture of several of them, and the reaction mass ratio of the polyaniline or polypropylene to the alkenyl nitrile compound is 1:3-2:1.

[0012] Furthermore, the hydroxylamine hydrochloride modification temperature is 50-120°C, the modification time is 4-36h, and the reaction mass ratio of polyacrylonitrile, polyaniline or polypropylene to hydroxylamine hydrochloride is 1:2-5:1. Preferably, sodium hydroxide is also added during the hydroxylamine hydrochloride modification process, and the molar ratio of sodium hydroxide to hydroxylamine hydrochloride is 3:1-1:1.

[0013] Preferably, before the electrospinning operation is performed, the spinning solution obtained above is filtered, and then a spinning aid is added to the spinning solution to make it have a certain viscosity to meet the spinning requirements.

[0014] The second aspect of the present invention provides a nanofiber for deep removal of copper complexes obtained according to the above preparation method.

[0015] The third aspect of the present invention provides the application of the above-mentioned nanofibers in the resource utilization of copper complex wastewater, including using nanofiber adsorbents to adsorb copper complex wastewater and using desorption liquid to desorb the copper complex, and obtaining a copper sulfate product through concentration, cooling crystallization, filtration and drying, wherein the desorption liquid is an aqueous sulfuric acid solution with a concentration of 0.5 to 2 mol / L.

[0016] The application also includes using a regeneration liquid to realize the recycling of the nanofibers, wherein the regeneration liquid is a sodium hydroxide aqueous solution with a concentration of 0.4 to 2 mol / L.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The invention uses polyacrylonitrile, polyaniline and polypropylene as raw materials, and uses chemical modification to introduce amidoxime groups under homogeneous conditions to obtain a nanofiber adsorbent with uniform and abundant surface attachment sites. The adsorbent interacts with the copper complex through nitrogen and oxygen atoms of specific structures, so that the copper complex undergoes phase transfer and is enriched on the surface of the nanofiber, thereby completing the deep treatment of the copper complex in the water body. The maximum adsorption capacity of the nanofiber adsorbent is 372.6 mg / g, and the adsorption equilibrium can be reached in 120 minutes. After desorption, the adsorbent can be regenerated and recycled, and the desorption enrichment liquid can be used to prepare a copper sulfate product, thereby realizing the resource utilization of wastewater containing copper complexes. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of the synthesis route of polyaniline-modified nanofibers described in Example 1;

[0020] Figure 2 This is the infrared spectrum of the polyaniline modified nanofibers described in Example 1;

[0021] Figure 3 a is the SEM image of the polyaniline modified nanofibers obtained in Example 1; Figure 3 b is the Mapping diagram of C element; Figure 3 c is the Mapping graph of N elements; Figure 3 d is the Mapping diagram of O element;

[0022] Figure 4 is an adsorption isotherm diagram of the polyaniline modified nanofiber to the copper complex;

[0023] Figure 5 is a diagram showing the adsorption kinetics of the polyaniline-modified nanofiber to the copper complex;

[0024] Figure 6 This is the breakthrough curve of polyaniline modified nanofibers in treating wastewater containing copper complexes;

[0025] Figure 7 This is a schematic diagram of the synthesis route of polyacrylonitrile modified nanofibers described in Example 2;

[0026] Figure 8 This is the infrared spectrum of the polyacrylonitrile modified nanofibers described in Example 2;

[0027] Fig. 9 a is the SEM image of the polyacrylonitrile modified nanofibers obtained in Example 2; Fig. 9 b is the Mapping diagram of C element; Fig. 9c is the Mapping graph of N elements; Fig. 9 d is the Mapping diagram of O element;

[0028] Fig.10 is an adsorption isotherm diagram of the polyacrylonitrile modified nanofiber to the copper complex;

[0029] Fig.11 is a diagram showing the adsorption kinetics of the copper complex by the polyacrylonitrile modified nanofiber;

[0030] Fig.12 This is the breakthrough curve of polyacrylonitrile modified nanofibers in treating wastewater containing copper complexes;

[0031] Fig.13 The XRD pattern of the copper sulfate product obtained. DETAILED DESCRIPTION

[0032] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.

[0033] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0034] Example 1

[0035] like Figure 1 The schematic diagram of the synthesis route of polyaniline modified nanofibers of the present invention is shown in FIG. 1 , and the preparation method specifically comprises the following steps:

[0036] (1) Preparation of polyaniline solution: 5 g of polyaniline was weighed and placed in a reactor, 70 mL of N,N-dimethylformamide was added thereto, and the mixture was heated at 90° C. to dissolve the polyaniline solution.

[0037] (2) adding 0.05 g of azobisisobutyronitrile and 10 mL of acrylonitrile to the polyaniline solution obtained in step (1), controlling the reaction temperature to 75° C. and the reaction time to 6 h; then adding 10 g of hydroxylamine hydrochloride and 12 g of sodium hydroxide, and reacting at 85° C. for 12 h;

[0038] (3) filtering the polyaniline reaction solution of step (2), obtaining nanofibers by electrostatic spinning technology, and obtaining polyaniline-modified nanofibers for deep removal of copper complexes by washing and drying.

[0039] The infrared spectrum of a polyaniline modified nanofiber for deep removal of copper complexes obtained by the above method is shown in FIG. Figure 2 , SEM and Mapping Figure 3 a-3d.

[0040] The method for conducting the copper complex adsorption isotherm and kinetics experiment using the polyaniline modified nanofibers obtained in Example 1 as an adsorbent is as follows:

[0041] (1) Adsorption isotherm experiment: Prepare copper complex solutions of different concentrations, weigh 20 mg of polyaniline-modified nanofiber adsorbent, and measure 20 mL of copper complex solutions of different concentrations, and perform static adsorption for 24 h. Determine the adsorption capacity of polyaniline-modified nanofiber adsorbent for copper complex under the conditions of copper complex solutions of different concentrations after adsorption equilibrium, see Figure 4 .

[0042] (2) Adsorption kinetics experiment: Prepare 100 mL of 500 mg / L copper complex solution, weigh 100 mg of polyaniline modified nanofiber adsorbent, and allow the polyaniline modified nanofiber adsorbent to fully contact with the copper complex solution. Determine the adsorption capacity of the polyaniline modified nanofiber adsorbent for the copper complex at different adsorption times. Figure 5 .

[0043] The maximum adsorption capacity of the polyaniline-modified nanofiber adsorbent for copper complex is 372.6 mg / g, and adsorption equilibrium can be reached in 120 minutes.

[0044] The adsorption effect of the polyaniline modified nanofiber adsorbent obtained by the above method on electroplating copper complex wastewater was tested: 2.0 g of the above adsorbent material was loaded into an adsorption column (diameter 10 mm, height 100 mm), and a peristaltic pump was used to control the copper complex wastewater to pass through the adsorption column from bottom to top at a flow rate of 1 mL / min. The effluent was taken at different times and its copper complex concentration was measured. Figure 6 From the penetration curve of the adsorbent for treating wastewater containing copper complexes, it can be clearly found that no copper complexes were detected in the effluent before 720 min. Therefore, the above-mentioned polyaniline-modified nanofiber adsorbent exhibits an excellent effect of deep removal of copper complexes.

[0045] Example 2

[0046] like Figure 7 The following is a schematic diagram of a synthetic route of polyacrylonitrile modified nanofibers. The preparation method specifically includes the following steps:

[0047] (1) Preparation of polyacrylonitrile solution: 5 g of polyacrylonitrile was weighed and placed in a reactor, 60 mL of N,N-dimethylformamide was added thereto, and the mixture was heated at 80° C. to dissolve the polyacrylonitrile solution;

[0048] (2) adding 4 g of hydroxylamine hydrochloride and 4 g of sodium hydroxide to the polyacrylonitrile solution obtained in step (1), and reacting at 85° C. for 12 h;

[0049] (3) filtering the polyacrylonitrile reaction solution of step (2), adding a certain spinning aid and obtaining nanofibers through electrostatic spinning technology, and obtaining a polyacrylonitrile modified nanofiber for deep removal of copper complexes through washing and drying.

[0050] The infrared spectrum of a polyacrylonitrile modified nanofiber for deep removal of copper complexes obtained by the above method is shown in Figure 8 , SEM and Mapping Fig. 9 a-9d.

[0051] The method for conducting the copper complex adsorption isotherm and kinetics experiment using the polyacrylonitrile modified nanofibers obtained in Example 2 as an adsorbent is as follows:

[0052] (1) Adsorption isotherm experiment: Prepare copper complex solutions of different concentrations, weigh 20 mg of polyacrylonitrile modified nanofiber adsorbent, and measure 20 mL of copper complex solutions of different concentrations, and perform static adsorption for 24 h. Determine the adsorption capacity of the copper complex by the polyacrylonitrile modified nanofiber adsorbent under the conditions of copper complex solutions of different concentrations after adsorption equilibrium, see Fig.10 .

[0053] (2) Adsorption kinetics experiment: Prepare 100 mL of 500 mg / L copper complex solution, weigh 100 mg of polyacrylonitrile modified nanofiber adsorbent, and allow the polyacrylonitrile modified nanofiber adsorbent to fully contact with the copper complex solution. Determine the adsorption capacity of the polyacrylonitrile modified nanofiber adsorbent for copper complex at different adsorption times. Fig.11 .

[0054] The maximum adsorption capacity of the polyacrylonitrile modified nanofiber adsorbent for copper complex is 205.0 mg / g, and adsorption equilibrium can be reached in 120 minutes.

[0055] The adsorption effect of the polyacrylonitrile modified nanofiber adsorbent obtained by the above method on electroplating copper complex wastewater was tested: 2.0 g of the above adsorbent material was loaded into an adsorption column (diameter 10 mm, height 100 mm), and a peristaltic pump was used to control the copper complex wastewater to pass through the adsorption column from bottom to top at a flow rate of 1 mL / min. The effluent was taken at different times and its copper complex concentration was measured. Fig.12 From the penetration curve of the adsorbent for treating wastewater containing copper complexes, it can be clearly found that no copper complexes were detected in the effluent before 420 min. Therefore, the above-mentioned polyacrylonitrile modified nanofiber adsorbent exhibits an excellent effect of deep removal of copper complexes.

[0056] After the nanofibers in the adsorption column in the above-mentioned Examples 1 and 2 are saturated with adsorption, a desorption liquid (2 mol / L sulfuric acid aqueous solution) can be pumped in from top to bottom for desorption, and then soaked in a regeneration liquid (2 mol / L sodium hydroxide aqueous solution) for regeneration and recycling. The copper ion desorption liquid enriched by multiple cycles of desorption is evaporated, concentrated, cooled, and crystallized to observe a large number of copper sulfate crystals. After filtering and drying, a copper sulfate product can be obtained, and its XRD shows Fig.13 , the product contains copper sulfate monohydrate and copper sulfate trihydrate.

[0057] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing nanofibers for deep removal of copper complexes, characterized in that: The preparation method comprises the following steps: (1) Modification using high molecular weight polymers such as polyacrylonitrile, polyaniline or polypropylene as raw materials; (2) obtaining the nanofibers by electrospinning the modified polyacrylonitrile, polyaniline or polypropylene solution; The modification is specifically as follows: when the raw material is polyacrylonitrile, it is directly modified with hydroxylamine hydrochloride; when the raw material is polyaniline or polypropylene, it is firstly modified with nitrile and then modified with hydroxylamine hydrochloride.

2. The preparation method according to claim 1, characterized in that: The hydroxylamine hydrochloride modification temperature is 50-120° C., the modification time is 4-36 hours, and the reaction mass ratio of the polyacrylonitrile, polyaniline or polypropylene to the hydroxylamine hydrochloride is 1:2-5:

1.

3. The preparation method according to claim 1, characterized in that: The nitrile modification is achieved by reacting polyaniline or polypropylene with alkenyl nitrile compounds and an initiator.

4. The preparation method according to claim 3, characterized in that: The nitrilization modification temperature is 50-90° C., and the reaction time is 2-12 hours.

5. The preparation method according to claim 3, characterized in that: The alkenyl nitrile compound is any one of acrylonitrile, butenedinitrile, butenenitrile, acrylonitrile, pentenenitrile, 3-cyclohexene-1-nitrile and methacrylonitrile, or a mixture of the two or more thereof. The reaction mass ratio of the polyaniline or polypropylene to the alkenyl nitrile compound is 1:3 to 2:

1.

6. The preparation method according to claim 3, characterized in that: The initiator is any one of potassium persulfate, ammonium persulfate, sodium persulfate, azobisisobutyronitrile and dicumyl peroxide or a mixture of the two or more thereof, and the amount of the initiator is 0.1% to 2% of the mass of the polyaniline or polypropylene.

7. A nanofiber for deep removal of copper complexes, obtained using the preparation method according to any one of claims 1 to 6.

8. An application of the nanofiber as claimed in claim 7 in the resource recovery of wastewater containing copper complexes, characterized in that: The application includes using nanofibers to adsorb wastewater containing copper complexes.

9. The use according to claim 8, characterized in that: The application also includes utilizing a desorption liquid to desorb the copper-containing complex and obtain a copper sulfate product, wherein the desorption liquid is a sulfuric acid aqueous solution.

10. The use according to claim 9, characterized in that: The application also includes using a regeneration liquid to achieve recycling of the nanofibers, and the regeneration liquid is a sodium hydroxide aqueous solution.

Citation Information

Cited By

  • Preparation method of foamed aluminum-based composite material for degrading sewage containing acid red G

    CN119746936A